Multimedia educational material and learning of Peruvian customs - Cárdenas-Valverde, Juan; Flores-Poma, Irina; Cárdenas-Valverde, Elí; Tovar, Nila; Corilla-Pérez, Renán; Corilla, Rocío (2022)
The objective of the research was to determine the effects produced by the multimedia educational material elaborated in Hypertext Markup Language for the learning of El Costumbrismo Peruano in the students of the fourth grade of secondary school of the Educational Institution "Jorge Basadre" of Chupaca (Peru). Specific: To establish the advantages and disadvantages that Hypertext Markup Language has in the elaboration of multimedia educational material for the learning of El Costumbrismo Peruano in the students of the fourth grade of secondary school of the Educational Institution "Jorge Basadre" of Chupaca. The research hypothesis was: The multimedia educational material elaborated in Hypertext Markup Language has significant effects for the learning of El Costumbrismo Peruano in fourth grade secondary school students of the Educational Institution "Jorge Basadre" of Chupaca. The research was of an applied type, due to the fact that the multimedia educational material was elaborated in the Hypertext Markup Language, demonstrating the practical form it has. The methods used in the investigation were: The scientific method; as a general method and the experimental and computerized methods; as specific methods. The research design used was the quasi-experimental with two research groups. The techniques used were: Observation and recording. Descriptive statistics were used in data processing and analysis techniques: arithmetic mean, median, mode and coefficient of variation; as well as inferential statistics for the validation and verification of the hypothesis. The main conclusion is: The application of the multimedia educational material elaborated in Hypertext Markup Language has significant effects on the learning of El Costumbrismo Peruano in students of the fourth grade of secondary school of the Educational Institution "Jorge Basadre" of Chupaca.
Keywords: multimedia educational material; secondary education; Peruvian customs